The effects of 2,4-D, BAP, and sucrose concentrations in the callus induction of white (Clitoria ternatea var. Albiflora) and blue butterfly pea (Clitoria ternatea) - Tengku Nurul Amira Aqma Tengku Zakaria; Hui, Shi Tan; Zurina Hassan; Sreeramanan Subramaniam; Bee, Lynn Chew (Penerbit Universiti Kebangsaan Malaysia, 2024)
The blue butterfly pea (Clitoria ternatea) and white butterfly pea (Clitoria ternatea var. Albiflora) belong to the Fabaceae family. Both are locally known as “bunga telang” and native to the Southeast Asian regions. The blue flowered variety is traditionally used to treat headaches, fever, and diabetes and is renowned scientifically for its memory-enhancing properties due to the presence of novel pentacyclic triterpenoids. However, farming of C. ternatea is challenged by inconsistent yields of novel secondary metabolites, especially under changing environmental conditions. Callus and cell suspension cultures, on the other hand, offer an alternative for the consistent production of these metabolites. The current study aims to optimize the treatments of 2,4-dichlorophenoxyacetic acid (2,4-D), 6-benzylaminopurine (BAP), and sucrose concentrations for friable callus formation from seedling explants. Sterile cotyledon explants of in vitro seedlings from both types of butterfly pea were subjected to half-strength MS medium supplemented with different concentrations and combinations of 2,4-D and BAP, with sucrose at 15 g/L and 30 g/L. The highest friable callus fresh weight from the white butterfly pea explants (0.064 ± 0.010 g) was achieved in treatments of 0.40 mg/L 2,4-D and 0.50 mg/L BAP. In contrast, the highest fresh weight of friable callus for the blue variety (0.025 ± 0.016 g) was induced in 0.25 mg/L of 2,4-D. Both varieties showed the highest friable callus weight in 15 g/L sucrose supplemented with 1.00 mg/L of 2,4-D (0.146 ± 0.032 g) and 0.25 mg/L of 2,4-D (0.245 ± 0.075 g) for the white and blue variety respectively. The morphology of calli for both varieties were yellowish, watery, and sticky. This study provides an essential basis the establishment of cell suspension cultures, as an efficient alternative to harness the secondary metabolites associated with the mammalian neuroprotective properties.